PELATIHAN INSTALASI WINDOWS KOMPUTER/LAPTOP PADA MASYARAKAT DESA PANGGUNG, KECAMATAN PELAIHARI - Billy; Khairul Anwar Hafizd; Rabini Sayyidati (Yayasan Lavandaia Dharma Bali, 2022)
Community service entitled “COMPUTER/LAPTOP WINDOWS INSTALLATION TRAINING IN DESA PANGGUNG COMMUNITIES, KECAMATAN PELAIHARI” has the aim of providing knowledge and skills for The Apparatuses of Desa Panggung in performing simple windows installations on their computers/laptops independently. The method used in carrying out this community service is to provide material directly and practice how to install Windows 10 on a laptop using virtual box tools. In addition, there was also a discussion method regarding the installation of windows with the participants. Community service in analyzing the level of understanding of the apparatus in the material that has been submitted by being given simple questions related to the material. The result of the activity based on the question and answer conducted between the participants and the presenters was an increase in knowledge about Windows Installation. The expected result of community service activities is that the participants can have knowledge in repairing their computers/laptops which includes the installation of the Windows operating system, installation of supporting software, and overcoming trouble if simple problems arise at any time.